Design and Development of Automatic Magnetic Setup for Hybrid Single-Point Diamond Turning of Optical Components - Shahrokh Hatefi; Khaled Abou-El-Hossein (Majlesi Journal of Electrical Engineering)
Single-Point Diamond Turning (SPDT) has been widely used in manufacturing of optical components for critical applications including military, defense, aerospace, computer science, electronics, medical, and dental. Magnetic Field (MF) assistance is a recent non-conventional assistive technique that could be used during SPDT process to improve the machining conditions. Recent experimental studies show that using MF assisted SPDT technique can improve the optical surface roughness compared to purely mechanical SPDT process. There are a few studies conducted on the application of magnetic manipulation technique during the SPDT process. The effects of applying a strong MF during diamond cutting on the outcome of the machining process, as well as the optimum MF parameters to be used in SPDT process, are not fully discovered yet. The purpose of this research is to design and develop an automatic MF assistance system that could be used in non-conventional MF assisted and hybrid SPDT processes. The proposed automatic system is capable of communicating with the hybrid controller and precisely set/modify the desired magnetic parameters, including the generated magnetic flux density, at the cutting zone. By using the proposed system, an automatic MF assistance system in non-conventional SPDT processes could be enabled and the optimum machining conditions could be determined.